Marketing plan for Sheera Food Industries Sdn. Bhd. A new product called 'Tamarind puree' / Mohamad Azlan Abdul Majid - Abdul Majid, Mohamad Azlan (2000)
The food processing business has become an important industry in the Malaysian economy. The increasing number of the total population made the demand for food consumption to increase. But there will be a shortage of food supply for the country if there is no development in the food industry. Sheera Food Industry is a food processing company. Food processing is categorized under manufacturing because the finished product goes through the "process" before it is distributed to the final user. The main reason to the existing of Sheera Food Industries is first to introduced its new product; called Sheera Tamarind Puree for household consumption. To introduce new product requires a lot of planning and implementation. While some products enjoy instant success, others require time and marketing effort before significant growth begins. So, a careful implementation and control of the marketing plan will ensure the success of the new product. Usually, when new product has a potential for rapid acceptance, producers will expect a vigorous competition. In this case, the plan should focus on the potential competitor. With slowly accepted product like the tamarind puree, the marketing strategy should focus on market development and product. In addition, because the final consumer purchases the product, the producer must also give attention to its production standards to ensure high quality standards of the product.